Municipality-level incidence of clinically diagnosed amyotrophic lateral sclerosis, multiple sclerosis and Parkinson's disease - Sipilä, Jussi; Jokela, Manu; Solje, Eino (Elsevier BV, 2026)
Background: The prevalences of Amyotrophic Lateral Sclerosis (ALS), Multiple Sclerosis (MS), and Parkinson's Disease (PD) have been shown to covary which suggests that they may share common pathogenetic factors.
Objective: Investigate the contemporaneous incidence patterns of ALS, MS, and PD on a municipal level in easternmost Finland.
Methods: Previously published ALS (years 2010–2018) and MS (years 2012–2016) cohorts were leveraged and PD data (years 2010–2018) were obtained from the national drug reimbursement entitlement registry. Population data were collected from a governmental registry.
Results: There were no municipalities with high incidences of all three disorders in both sexes. An ALS hotspot was observed in southeastern municipality of Tohmajärvi, driven by men. PD incidence was lowest in the central municipalities, around the urban area. Age-adjusted ALS and PD incidence was high and MS incidence low in Nurmes. Analyses of ALS and PD incidences using population aged >45 as reference showed an area of low PD incidence in the westernmost municipalities but no clear ALS incidence pattern. No municipality showed a high incidence of both disorders but the ones with the highest incidences are neighboring municipalities (Tohmajärvi and Kitee) in the southern part of the province. There was no correlation between ALS and PD incidence (p = 0.17).
Conclusions: Contemporaneous incidences of ALS, MS, and PD showed no correlations. These results suggest that epidemiological research for their common pathogenic factors needs to employ very long study periods and birth cohorts in large populations. Neuropathological and/or biomarker validation of cases should also be included whenever possible.